Beyond the megacity new dimensions of peripheral urbanization in Latin America - Reis, Nadine; Lukas, Michael (Geographer) (Global suburbanisms., 2022)
"Beyond the Megacity connects and reconnects the global debate on the contemporary urban condition to the Latin American tradition of seeing, considering, and theorizing urbanization from the margins. It develops the approach of "peripheral urbanization" as a way to integrate the theoretical agendas belonging to global suburbanisms, neo-marxist accounts of planetary urbanization, and postcolonial urban studies, and to move urban theory closer to the complexity and diversity of urbanization in the Global South. From an interdisciplinary perspective, Beyond the Megacity investigates the natures, causes, implications, and politics of current urbanization processes in Latin America. The book draws on case studies from various countries across the region covering different theoretical and disciplinary approaches from the fields of geography, anthropology, sociology, urban studies, agrarian studies, and urban and regional planning, and is written by academics, journalists, practitioners, and scholar-activists. Beyond the Megacity unites these unique perspectives by shifting attention to the places, processes, practices, and bodies of knowledge that have often been neglected in the past."--